Resources Support Strategy Department of Tourism, Youth and Sports in the Development of Tourism Objects - Devi Dwi Kristanti; Ilmi Usrotin Choiriyah (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to analyze and describe the Strategy of the Department of Tourism, Youth and Sports in Developing the Coban Canggu Tourism Object. The research method used is descriptive qualitative with data collection techniques through interviews, observation and documentation. By using purposive sampling technique in determining informants. The results of research in the resources support strategy of the Department of Tourism, Youth and Sports in Developing Coban Canggu Tourism Objects, Pacet District, Mojokerto Regency, show that utilizing existing resources, both in the provision of infrastructure, human resources, and budgets. As there is still a lack of available budget, the slow pace of developing the Coban Canggu Waterfall attraction has not been maximized.